Culturally responsive teaching online & in person an action planner for dynamic equitable learning environments - Budhai, Stephanie Smith; Lewis Grant, Kristine S. (Corwin teaching essentials, 2022)
"With the onset of COVID-19, K-12 educators across the United States were thrown into online teaching and learning. In the translation of lesson plans into online instruction, teachers needed to attend to their students' academic and socioemotional needs. At the same time, while the nation was dealing with the pandemic, civil unrest was heightened. There is now a more pronounced focus on issues of equity, inclusion, and social justice. Many teachers were not trained on how to address these issues in the classrooms. However, culturally responsive pedagogy can be used to provide teachers with a framework to guide their teaching of diverse learners. Moreover, with the one-year anniversary of schools shutting down, many schools are now starting to transition to part-time and in-person learning, but keeping elements of online learning while needing to address issues of diversity. This book addresses both of these issues - incorporating equity and diversity across a range of learning environments. There are no resources currently available that address embedding culturally responsive teaching across in-person, online, and simultaneous learning settings. This book will provide teachers with a toolkit that will not only inspire them, but help them to translate their care and concern for students into their online classrooms. Culturally responsive teaching has enabled K-12 educators to foster inclusive classrooms and facilitate student learning. However, online teaching presents a new space for teachers to imagine how they might support and engage students across diverse cultural and linguistic backgrounds. Because teachers will be charged with students in, in-person, online, and simultaneous learning environments, this book will offer K-12 educators demonstrative, inspirational, and practical approaches to culturally responsive instruction across any educational setting"--